Impact of “Enhanced Recovery After Surgery” (ERAS) protocols vs. traditional perioperative care on patient outcomes after colorectal surgery: a systematic review - Vaishnavi Kannan; Najeeb Ullah; Sunitha Geddada; Amir Ibrahiam; Zahraa Munaf Shakir Al-Qassab; Osman Ahmed; Iana Malasevskaia (Patient Safety in Surgery)
Abstract Background Colorectal surgery is associated with a high risk of postoperative complications, including technical complications, surgical site infections, and other adverse events affecting patient safety and overall patient experience. “Enhanced Recovery After Surgery” (ERAS) is considered a new standard of care for streamlining the perioperative care of surgical patients with the goal of minimizing complications and optimizing timely patient recovery after surgery. This systematic review was designed to investigate the evidence-based literature pertinent to comparing patient outcomes after ERAS versus conventional perioperative care. Methods This systematic review evaluates the performance of ERAS protocols against conventional care in colorectal surgery, focusing on various postoperative outcome measures. An extensive search was conducted across multiple electronic databases and registers from July 2 to July 5, 2024, complemented by citation searching on November 30, 2024. This approach led to the identification of 11 randomized controlled trials (RCTs) from the past decade, involving 1,476 adult participants. To ensure methodological rigor and transparency, the review followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2020 guidelines and was registered with PROSPERO (CRD42024583074). Results The implementation of ERAS protocols resulted in a notable decrease in hospital stay duration compared to conventional care, with reductions varying between 3 and 8 days across studies. ERAS patients also had faster gastrointestinal recovery, including quicker times to bowel movement, defecation, and resumption of normal diet. Furthermore, patients in ERAS groups showed notably reduced postoperative complications and opioid consumption, with patients experiencing lower pain scores on the Visual Analogue Scale (VAS) and reduced reliance on opioids. Additionally, nutritional recovery in ERAS patients was enhanced, with elevated albumin and total protein levels, alongside decreased inflammatory markers and improved immune function. Conclusion This systematic review provides compelling evidence supporting the integration of ERAS protocols into standard colorectal surgical practices. Future studies should aim to explore the variations in ERAS implementation, pinpoint the most impactful elements of ERAS, and work towards personalizing and standardizing these protocols across clinical settings. Additionally, evaluating long-term outcomes will help refine ERAS strategies, ensuring their enduring impact on patient recovery.